THE POTENTIAL OF THE PEOPLE'S MARKET IN BALI AS A TOURISM ATTRACTION BASED ON BALI CULTURE TOURISM - Ida Ayu Made Dwi Susanti; Luh Putu Kirana Pratiwi; Nyoman Yudiarini (International Journal of Applied Science and Sustainable Development (IJASSD), 2022)
The people's market is one of the most tangible indicators to see the level of economic life of the surrounding community. The people's market does not only involve economic actors in the agricultural and food sectors but also non-agricultural actors such as financial service actors and transportation service actors whose existence is indirectly very meritorious (Firmanzah and Halim, 2012). The approach to the agricultural sector that is still being carried out today is the approach through the agribusiness system. As a people's market that is also visited by tourists, the People's Market in Bali must meet the requirements of a healthy market, with Indonesian national standards, and standards for organizing Balinese cultural tourism. The People's Market in Bali has the potential to be developed as a tourist attraction. The intended tourist attraction is the type of Balinese Cultural Tourism.